List of Competed Master Dissertation January 2010 to December 2011 - Editor, The (Journal of Nepalese Business Studies, 2012)
The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page : 120-125 Uploaded date: July 8, 2012